Association of maternal folic acid supplementation and offspring MTRR gene polymorphism with congenital heart disease: a hospital-based case-control study in Han population - Liuxuan Li; Jun Ou; Yige Chen; Qian Chen; Manjun Luo; Tingting Wang; Yingfan Zhang; Jiabi Qin (Journal of Health, Population and Nutrition)
Abstract Background Although many studies shown that the risk of congenital heart disease (CHD) was closely related to genetic and environmental factors, the exact mechanism was still unclear. This study was to assess the association of maternal folic acid supplementation (FAS), the 5-methyltetrahydrofolate-homocysteine methyltransferase reductase (MTRR) gene polymorphisms in offspring and their interaction effects with the risk of CHD and its subtypes. Methods A case-control study was conducted on 595 children with CHD and 605 healthy child controls. The multivariate logistic regression model was used to assess the association of maternal FAS, offspring MTRR gene polymorphisms and their interaction effects with CHD and its subtypes. Results This study shown that maternal FAS was significantly associated with a reduced risk of CHD (OR = 0.55, 95%CI: 0.36–0.83) and its subtypes including ASD (OR = 0.25, 95%CI: 0.14–0.45), VSD (OR = 0.42, 95%CI: 0.27–0.64), and CTD (OR = 0.23, 95%CI: 0.09–0.59) in offspring. Offspring MTRR gene polymorphisms at rs162048 (GG vs. AA: OR = 2.05, 95%CI: 1.35–3.13), rs1802059 (AA vs. GG: OR = 5.13, 95%CI: 2.15–12.23; GA vs. GG: OR = 1.81, 95%CI: 1.35–2.43), rs10380 (TT vs. CC: OR = 2.27, 95%CI: 1.20–4.31) and rs1801394 (GG vs. AA: OR = 1.58, 95%CI: 1.02–2.42) were significantly associated with the risk of CHD, and similar results were also found for three subtypes of CHD. Additionally, a statistically significant interaction effect between maternal FAS and offspring MTRR gene polymorphism at rs1802059 was observed (OR = 0.38, 95%CI: 0.15–0.94). Among children who had a variant genotype at rs1802059, the risk of CHD was significantly decreased when their mother used folate for this pregnancy compared with mothers not using folate. Conclusions In those of Chinese descent, maternal FAS and offspring MTRR gene polymorphisms are significantly associated with the risk of CHD and its three subtypes. Furthermore, maternal FAS may help to offset some of risks of CHD due to offspring MTRR genetic variants. However, more studies with prospective designs and larger samples are needed to confirm our findings. Trial registration Registration number: ChiCTR1800016635; Registration time: 14/06/2018.